National land use management in China: An analytical framework - Haoying Han; Shih-Kung Lai (Journal of Urban Management, 2012)
Rapid urban land growth has been a major characteristic of urbanization in China since reform and open-door policies began in the late 1970s. Due to its unique political system, historical experience, and geographic conditions, urban land growth in China is still characterized by short periods of land acquisition, large-scale land development, and large-scale industrial use. Although urban land use is basically a local issue for cities, many important policies are also framed by the Chinese central government to ensure that national interests are protected. Following a review of urban land growth in China, this study found that the role of the central government in urban land growth has been changing in recent years. The once exclusive objective of ensuring urban economic development has been replaced by multi-objective considerations of economic, social, and environmental issues, addressing both urban and rural interests in the process of urban land growth. This transition has also greatly influenced the policies of city governments, which has in turn influenced local land use patterns. However, attaining these multiple objectives is becoming increasingly difficult. This paper examines the underlying causes of this shift and discusses various approaches to adjusting the future role of the central government.
Keywords: 710; China; game theory; garbage can; National land policy